Dicyclohexyl{3-hydroxy-N `-[1-(2-oxidophenyl-kappa O)ethylidene]-2-naphthohydrazidato-kappa N-2 `,O}tin(IV) - Lee, S.M.; Ali, H.M.; Lo, K.M.; Ng, S.W. (International Union of Crystallography, 2010)
In the title compound, [Sn(C6H11)(2)(C19H14N2O3)], the Sn-IV atom is O,N,O' chelated by the deprotonated Schiff base ligand and exists in a cis-trigonal-bipyramidal environment, completed by the two cyclohexyl ligands.